Design and Performance Analysis of Blades Based on the Equal–Variable Circulation Method - Liang, D.; Song, C.; Liang, S.; Wang, S.; Li, Y.; Zhou, Z. (Frontiers in Energy Research, 2021)
With the aim of improving the aerodynamic performance of axial turbomachinery, a new type of blade is designed using the equal–variable circulation method. Taking an axial flow fan as the research object, this article describes the development of a new type of turbomachinery by changing the design method and producing a blade with forward sweep. The aerodynamic performance of the fan is simulated and compared with the experimental data. The numerical results show that the equal circulation design method improves the aerodynamic performance of the blade roots, while the variable circulation design method enhances the aerodynamic performance of the blade tips. By adopting the equal–variable circulation design method, the total pressure of the experimental fan is increased by about 4%, while the efficiency remains unchanged. Forward-swept blades with an equal–variable circulation design also improve performance over the conventional blades by changing the center-of-gravity stacking line. At low flow rates, the efficiency of the experimental fan can be increased by 7.5%, and the working range of the flow is expanded. Under high flow rates, the restriction of the blade tip on the airflow is decreased and the fluidity is slightly reduced.